The metaphysics of gender - Witt, Charlotte, 1951- (New York ; Oxford : Oxford University Press, 2011)
'The Metaphysics of Gender' is a book about gender essentialism what it is and why it might be true.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gender identity -- Philosophy; Essentialism (Philosophy)